Comparison of Domiciliary and Institutional Delivery-care Practices in Rural Rajasthan, India - Iyengar, Sharad D; Iyengar, Kirti; Suhalka, Virendra; Agarwal, Kumaril (Journal of Health, Population and Nutrition, 2009)
A retrospective cross-sectional survey was conducted to assess key practices and costs relating to home- and institutional delivery care in rural Rajasthan, India. One block from each of two sample districts was covered (estimated population-279,132). Field investigators listed women who had delivered in the past three months and contacted them for structured case interview. In total, 1,947 (96%) of 2,031 listed women were successfully interviewed. An average of 2.4 and 1.7 care providers attended each home- and institutional delivery respectively. While 34% of the women delivered in health facilities, modern care providers attended half of all the deliveries. Intramuscular injections, intravenous drips, and abdominal fundal pressure were widely used for hastening delivery in both homes and facilities while post-delivery injections for active management of the third stage were administered to a minority of women in both the venues. Most women were discharged prematurely after institutional delivery, especially by smaller health facilities. The cost of accessing home-delivery care was Rs 379 (US$ 8) while the mean costs in facilities for elective, difficult vaginal deliveries and for caesarean sections were Rs 1,336 (US$ 30), Rs 2,419 (US$ 54), and Rs 11,146 (US$ 248) respectively. Most families took loans at high interest rates to meet these costs. It is concluded that widespread irrational practices by a range of care providers in both homes and facilities can adversely affect women and newborns while inadequate observance of beneficial practices and high costs are likely to reduce the benefits of institutional delivery, especially for the poor. Government health agencies need to strengthen regulation of delivery care and, especially, monitor perinatal outcomes. Family preference for hastening delivery and early discharge also require educational efforts. Key words: Childbirth; Cross-sectional studies; Emergency care; Fundal pressure; Knowledge, attitudes, and practice; Labour; Obstetric care; Oxytocin; Retrospective studies; Traditional birth attendants; India doi: 10.3329/jhpn.v27i2.3371 J Health Popul Nutr 2009 April;27(2):303-312